ORAL HEALTH OF THE ELDERLY IN BRAZIL: SYSTEMATIC REVIEW - Paraguassu, Éber Coelho; Lacerda, Jamille dos Passos (Brazilian Journal of Implantology and Health Sciences, 2019)
Introduction: The Brazilian population has undergone demographic changes over the years. This increase in life expectancy has resulted in the growth of the country’s elderly population, necessitating giving people a aging with quality of life. Objective: to report the oral health conditions of the Brazilian elderly, emphasizing the quality of life of the elderly, as well as the knowledge of the caregivers regarding the hygiene and maintenance of the oral health of this population. Material and method: This is a bibliographical study, approaching the search of articles published in the last five years in Google Scholar and Scopus about "Oral Health Conditions of the Elderly in Brazil". The following descriptors were used: "dentistry", "elderly" and "oral health of the elderly". In the screening of articles, using the inclusion criteria, nineteen articles were studied, of which six articles published in 2014, nine articles published in 2015 and four articles published in 2019. Conclusion: One can conclude with this work that there is a need for dental treatment aimed at this population, due to the pathologies from aging itself.